Афролимнофила (Afrolimnophila А l.) — новый для палеоарктической фауны подрод комаров-лимониид (Diplera. Iimoniidae) - Савченко, Е.Н. (Вестник зоологии, 1971)
The Limoniid-flies subgenus Afrolimnophila A 1. is recognized for the first lime in the palaearctic region. Three new Transcaucasian species from this subgenus are described. Their differences are as follows: 1(2). Wings unpatterned except for the well defined blackish stigma. Femora and tibiae only vaguelly and narowly darkened at the tips. Male hypopyg — Fig. 3. Terra typica — Talysh L. (A.) abludens S a v. sp. n. 2(1). Wings heavily patterned with brownish-black. Femora and tibiae abruptly and broadly darkened at the tips. Male hypopyg — Figs. 1 and 2. 3(4). Mesonotal praescutum brown striped. Wings without brownish-black clouds in the cells R2 and M. Male hypopyg — Fig. 1. Terra typica — Nakhichevan Autonomous SSR . . .. . . L. (A.) minima S a v. sp. n. 4(3). Mesonotal praescutum unstripped. Wings with brownish-black clouds in the cells R2 and M. Male hypopyg — Fig. 2. Terra typica — South-western Georgia L. (A.) basispina S a v. sp. n. The typical specimens of all the three new species are preserved in the collection of the Institute of Zoology in Kiev.